2009
DOI: 10.1007/s10661-008-0743-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of contaminant impacts in a semi-enclosed estuary (Amvrakikos Gulf, NW Greece): Bioenergetics and biochemical biomarkers in mussels

Abstract: A combination of bioenergetics and biochemical biomarkers in mussels was applied to assess possible pollution impacts in a protected semi-enclosed estuary (Amvrakikos Gulf, NW Greece) that receives pesticide discharges through riverine transport. Scope for growth, a physiological condition index representing the energy budget of the organism, was applied to detect general stress effects on the health status of mussels. The low energy budgets of mussels revealed stress conditions and provided early warning sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…We examined the relationship between metabolic rate and SFG by reviewing literature using the search term “scope for growth“ in Google Scholar and Web of Science. We compiled studies that reported both SFG calculation and measured respiration (i.e., oxygen consumption or metabolic rate; Widdows et al , ; Sobral and Widdows ; Smolders et al ; Halldorsson et al ; Neuberger‐Cywiak et al ; Tsangaris et al , ; Fernández et al ). We also collected clearance rate data when reported.…”
Section: Defining Bioenergetics‐aopmentioning
confidence: 99%
“…We examined the relationship between metabolic rate and SFG by reviewing literature using the search term “scope for growth“ in Google Scholar and Web of Science. We compiled studies that reported both SFG calculation and measured respiration (i.e., oxygen consumption or metabolic rate; Widdows et al , ; Sobral and Widdows ; Smolders et al ; Halldorsson et al ; Neuberger‐Cywiak et al ; Tsangaris et al , ; Fernández et al ). We also collected clearance rate data when reported.…”
Section: Defining Bioenergetics‐aopmentioning
confidence: 99%
“…( 2005, 2008 , Fernández et al ( 2010 ) , Bartolomé et al ( 2010b ) , Jovic et al . ( 2011 ) , and information of direct ecological signifi cance, Costas-Rodríguez et al ( 2010 ) , Tsangaris, et al ( 2010 ) and potential relevance to human health, Culha et al ( 2008 ) . Seafood is a major source of animal protein and very rich sources of mineral components, Fuentes et al ( 2009) , Ozden et al ( 2010 .The health benefi ts associated with the consumption of seafood products are particularly important for the prevention of heart-related diseases and for many vulnerable groups, such as pregnant and lactating women, infants and children, Cozzolino et al .…”
Section: Introductionmentioning
confidence: 99%
“…4 ), indicating exposure to compounds that cause oxidative stress. Antioxidant enzymes can be induced by enhanced production of ROS as a protective mechanism against oxidative stress, or they can be inhibited when deficiency of the system occurs, suggesting toxicity [ 62 ]. In this study, significant increase in oxidative stress as measured by ROS concentrations as well as LPO and PCC occurred in snails exposed at both sampling locations.…”
Section: Discussionmentioning
confidence: 99%